Relationship between Photosynthetic Rate and Stomatal Conductance, Intercellular CO2 Concentration, Transpiration Rate, Vapour Pressure Deficit and Photosynthetically Active Radiation in Sweet Corn (Zea mays) - Khamis, Aidee Kamal (Journal of Sustainable Natural Resources, 2020)
Corn plantation is number three largest plantation crops nowadays in Malaysia. Thus the reproductive process is critical to ensure the corn yield. Photosynthesis activities is one of the major elements which can be measured the corn plantation reproductive process during plantation. Through this photosynthesis activities, we can plan what is the best time to apply the corn plantation nutrients along the corn plantation until harvesting process. In the beginning of this study, the seeds were planted at a distance of 10 cm both between plants and rows. A total of eight subplots of 2.2 meter long, 60 cm wide and 30 cm high were prepared as Randomized Complete Block Design (RCBD). The photosynthesis activities was measured at day 10, 20, 30, 40, 50 and 60 around 9:00 am in the morning and 4:00 pm in the evening. Three uniform plants, one from each replicate were selected and the same leaf were sampled throughout the experiment. As a results, after day 30 and above, as an average, even the stomatal conductance still maintain opened, the other parameters such as intercellular CO2 concentration, transpiration rate, vapour pressure deficit base on leaf temperature and phosynthetically active radiation is going to decrease until the harvesting date. The energy for photosynthesis activity for vegetative process is valid start from early plantation until day 30. After day 30, it diverted to the photosynthesis activity to reproductive process to produce corn cobs.